1999
DOI: 10.1038/sj.bjc.6690148
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies against p53 in relation to cancer risk and prognosis in breast cancer: a population-based epidemiological study

Abstract: To perform an epidemiological evaluation of the predictive value of p53 autoantibodies in breast cancer, we measured antibodies against p53 in serum samples from 165 breast cancer patients in comparison with serum samples from 330 healthy controls, selected from the same population as the cases and matched for age, sex and specimen storage time. Median age of patients was 51 years (range 25–64 years). Presence of serum p53 autoantibodies was analysed by enzyme-linked immunosorbent assay (ELISA) and confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 21 publications
1
47
0
1
Order By: Relevance
“…In breast cancer, particular interest in such correlations has focused on anti-53 autoantibodies, where some studies observed a correlation between poor prognosis and increased levels of anti-53 autoantibodies (70,71), although these results could not always be confirmed by others (72). It may, therefore, seem surprising that the favorable prognosis of MCB correlates with anti-actin autoantibodies.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In breast cancer, particular interest in such correlations has focused on anti-53 autoantibodies, where some studies observed a correlation between poor prognosis and increased levels of anti-53 autoantibodies (70,71), although these results could not always be confirmed by others (72). It may, therefore, seem surprising that the favorable prognosis of MCB correlates with anti-actin autoantibodies.…”
Section: Discussionmentioning
confidence: 76%
“…Autoantibodies observed in some tumors may be due to large tumor masses and necrosis exposing a large amount of autoantigen to the immune system. Alternatively, as suggested for p53, in which mutations have been found to be associated with more aggressive tumors and poorer prognosis of breast cancer, the mutated p53 tends to have a much longer half-life than the wild-type p53, leading to accumulation of the protein and anti-p53 Ab production (70,71). In contrast, the anti-actin Abs observed in MCB are probably a result of increased tumor cell apoptosis; thus, these Abs serve as a marker of a beneficial biologic process.…”
Section: Discussionmentioning
confidence: 99%
“…These results have shown varying levels of positivity for p53-Abs in all cancer types but with less than 0.5% of healthy controls being positive. The presence of p53-Abs have been associated with a worse prognosis in breast (Peyrat et al, 1995;Lenner et al, 1999), head and neck (Bourhis et al, 1996) and colon cancer (Houbiers et al, 1995;Kressner et al, 1998). In NSCLC early reports of p53 mutation suggested a variable relationship to survival (McLaren et al, 1992;Quinlan et al, 1992;Lee et al, 1995).…”
mentioning
confidence: 99%
“…Analysis of a broad spectrum of autoantibodies is increasingly used in predictive diagnostics of autoimmune diseases (3 ), and autoantibodies against oncogene products are being studied in predictive oncology (4 ). The most interesting medical application, however, would be to rapidly assay the spectrum of microbiological agents to which a person has been exposed because past infections can be highly predictive of the risk of future diseases.…”
mentioning
confidence: 99%